General knowledge and need for cognition – Is there a mediating role of behavioral habits? - Huić, Aleksandra (Array, 2008)
Personality and behavioral correlates of general knowledge were examined. General knowledge was assessed with an advanced vocabulary test (consisting of words of latin and greek origin). Need for Cognition Scale (Caccioppo and Petty, 1992) was administered, along with questions about behavioral habits in relation to theaters, museums, movies and libraries. We also assessed the respondents exposure to different kinds of media information – TV, radio, Internet, daily news, scientific and entertainment magazines and books. Total of 600 respondents (50% male and 50% female ; 49% high school and 51% higher education) participated in the study. Applied and theoretical implications are discussed.